Assessment of facultative anaerobes from the root canals of deciduous molars: An in vivo study - Manisha Chandwani; Shweta Chandak (Tabriz University of Medical Sciences, 2017)
Background. The current research aimed to assess the prevalence of facultative anaerobes isolated from the root canals of deciduous molars. Methods. The present research enrolled 60 children in the 6‒9-year age group based on clinical and radiographic findings. Under aseptic conditions, access cavities were prepared followed by collection of samples from infected root canals with the help of sterile paper points. The samples thus obtained were subjected for microbial assay. Results. It was found that Enterococcus faecalis was isolated in 30% of cases, Escherichia coli in 28.4%, Staphylococcus aureus in 25%, α-hemolytic Streptococci in 15% and Proteus mirabilis in 1.6% of cases. Conclusion. It was concluded from the results of the present study that the root canals of deciduous molars had predominance of facultative anaerobes, confirming its polymicrobial nature. This identification of microbes is crucial as it aids in understanding the pathogenesis of pulpal and periradicular diseases to provide effective antimicrobial irrigation and medicament for endodontic treatment.